The determination of the effect of Curcumin on Saccharomyces cerevisiae totally protein expression changes and cell growth - Beyaz, Seda; Gok, Ozlem; Aslan, Abdullah (Progress in Nutrition, 2021)
The use of turmeric for the treatment of various diseases stems mainly from its active biological functions, namely anti-inflammatory, antioxidant, anti-microbial, anti-alzheimer, anti-tumor, anti-diabetic and anti-rheumatism activities. Turmeric is a hypoglycemic, hepatoprotective, nephroprotective, cardioprotective and neuroprotective molecule, and it is reported to suppress thrombosis and protect against myocardial infarction. In this study, four groups were formed to investigate whether Curcumin has a protective role against the damage caused by hydrogen peroxide (H2O2) in Saccharomyces cerevisiae. Groups: (i) Control Group: Yeast cultivated group only; (ii) Curcumin Group: Curcumin group (% 8); (iii) H2O2 Group: Group given H2O2 (15 mM); (iv) Curcumin + H2O2 Group: Group given Curcumin (% 8) + H2O2 (15 mM). Saccharomyces cerevisiae cultures were developed at 30 °C for 1, 3, 5 and 24 hours. Cell growth, lipid peroxidation MDA (malondialdehyde) analysis and GSH (glutathione) levels were determined by spectrophotometer. Total protein changes were detected by SDS-PAGE electrophoresis and calculated by Bradford method. According to the results obtained; Cell growth (1, 3, 5 and 24 hours), total protein synthesis and GSH levels (24 hours) increased in Curcumin groups, while MDA level decreased (24 hours) when compared with H2O2 group. As a result, it was determined that Curcumin Saccharomyces cerevisiae culture has an effect that promotes cell growth and total protein synthesis as well as reducing oxidative damage.